Effects of acute cigarette smoke exposure on macrophage kinetics and release of tumour necrosis factor α in rats - G. P. Pessina; L. Paulesu; F. Corradeschi; E. Luzzi; A. Di Stefano; M. Tanzini; G. Matteucci; V. Bocci (Mediators of Inflammation)
Some biological parameters before and after an acute episode of cigarette smoking in rats have been evaluated. The carboxyhaemoglobin levels depended either on the number of cigarettes, or on the time of exposure to cigarette smoke and returned to pre-smoking values in about 2 h. The evaluation of the kinetics of alveolar and peritoneal macrophages in rats after a smoking session of three cigarettes within an hour, indicated that alveolar macrophages in the bronchoalveolar lavage fluid significantly increased 8 h after the smoking, whereas the number of peritoneal macrophages remained practically constant. The incubation of these cells for various times at 37°C in a humidified atmosphere, resulted in a spontaneous release, 24 h thereafter, of variable amounts of tumour necrosis factor α (TNFα), which remained practically constant during the following days. Neither alveolar macrophages of control rats, nor peritoneal macrophages of both control and smoking rats were able to release TNFα. Moreover, after lipopolysaccharide induction of alveolar macrophages of both control and smoking rats, an increased release of TNFα was observed, indicating that these cells were in an active state.